How to write a winning recommendation letter for Master and PhD candidates : - Nazari, Reza (CreateSpace Independent Publishing Platform, 2017)
This book offers 100 sample letters of recommendation for master and PhD candidates. The sample letters are provided by university and college professors for their students, with various academic backgrounds. These letters helped the candidates gain admittance into their desire programs in esteemed universities around the world.